Microplastics leaching from baby products - Heng, Serene Hwee Fen (Nanyang Technological University, 2020)
Plastics is prevalent and ubiquitous in our modern daily lives, and the rapid plastic production has led to the myriad applications of plastics. Microplastics found in marine animals and organisms will ultimately be absorbed by the tissue of higher trophic animals upon consumption. Microplastics have also been found in human consumables and human organs such as the lungs. Recent studies have shown that an infant consumes millions of microplastics due to the use of infant plastic products. In addition, studies have suggested that there are leaching fibres from washing of textiles. Infants are exposed to soft toys every day and because they have a lot of hand-to-mouth activity, they are at high risk of consuming the microplastics leaching from soft toys. Thus, the purpose of this project was to investigate the potential polymers leaching out from the soft toys and quantify the microplastics leaching from baby products. In this study, 4 sample toys (Eeyore, Squirrel, Koala and Cat) were experimented on and analysed for the data results. Glass wares were used throughout the project to limit the cross-contamination of plastics and therefore, preventing false-positive results. The soaking and filtration method was standardized during the study. Nile Red (NR) was used as a staining agent to identify microplastics under confocal and fluorescence microscope. In addition, Scanning Electron Microscopy (SEM) was used to observe the morphology of the particles. Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GCMS) was adopted to identify the polymer type and additives from the soft toys and Fourier-Transform Infrared Spectroscopy and Raman Spectroscopy (FTIR) was used as a complementary method. Quantification of microplastics was conducted using confocal technique. Furthermore, a brief preliminary experiment was conducted to observe the trend of fibres released as the number of washing cycle increases. The results from Py-GCMS suggested that the polymer found on Eeyore was Polyethylene Terephthalate (PET) as the major microplastic, followed by Polyacrylonitrile (PAN) and Polydimethylsiloxane (PDMS). Furthermore, FTIR also suggested that that the material was PET. After soaking Eeyore in filtered MilliQ (FMQ), the leaching microplastic was identified under Py-GCMS as PDMS. Confocal showed that after soaking the soft toys in FMQ, the microplastics leaching is 108 fibres per washing. The trend could suggest that leaching can last quite a long time in the soft toys even after washing and drying for a long time. Thus, the infants could be at high risk of consuming large amount of microplastics.